Hemostatic profile changes in patients with traumatic brain injury with regard to the genotypes of -675 4G/5G polymorphism of plasminogen activator inhibitor-1 gene - O. O. Potapov; O. P. Kmyta; N. S. Shekera; K. A. Pabot (Zaporožskij Medicinskij Žurnal)
Traumatic brain injury (TBI) is a significant problem in modern clinical medicine that has both medical and social importance. Analysis of hemostatic changes is a very important aspect of clinical course of TBI and should be paid special attention on it. This analysis is necessary to make prognosis for the treatment outcomes taking into account associations with genetic factors.